The effect of hydrogen adsorption on the magnetic properties of Fe adatoms on Si(001) - Kishi, Tomoya (Animo Repository, 2004)
We investigate the magnetic properties for Fe adatoms on Si(001) on the basis of first-principles calculations. For the Si(001) surface, we consider systems having buckling dimers and H-terminated symmetric dimers. We find that the magnetic moment of the Fe adatom on the latter surface is larger than that of the Fe adatom on the former surface. The results positively indicate potential applications in the realization/fabrication of nanospintronics devices.